Attenuation of neuropsychiatric symptoms and caregiver burden in Alzheimer's disease by motor intervention: a controlled trial - Stella, Florindo [UNESP]; Canonici, Ana Paula [UNESP]; Gobbi, Sebastião [UNESP]; Galduroz, Ruth Ferreira Santos [UNESP]; Cação, João de Castilho; Gobbi, Lílian Teresa Bucken [UNESP] (Universidade de São Paulo (USP), Faculdade de Medicina, 2011)
OBJECTIVE: To analyze the effects of motor intervention on the neuropsychiatric symptoms of Alzheimer's disease and on the caregivers' burden. DESIGN: This is a controlled trial evaluating the effects of a motor intervention program on the neuropsychiatric symptoms. SETTING: The intervention was performed on community patients from two university centers specializing in physical exercise for the elderly. SUBJECTS: Patients with Alzheimer's disease were divided into two groups: sixteen received the motor intervention and sixteen controls (five controls were excluded because of clinical intercurrences). INTERVENTIONS: Aerobic exercises (flexibility, strength, and agility) and functional balance exercises were conducted over six months for 60 minutes three times per week. MAIN MEASURES: Psychopathological features of patients were evaluated with the Neuropsychiatric Inventory and Cornell Scale for Depression in Dementia. Caregivers were evaluated using the Neuropsychiatric Inventory-Distress and Burden Interview. A two-way analysis of variance (ANOVA) was applied to observe interactions (pre- vs. post-intervention; participants vs. controls). RESULTS: Patients from the intervention presented a significant reduction in neuropsychiatric conditions when compared to controls (Neuropsychiatric Inventory: F: 11.12; p = 0.01; Cornell Depression scale: F: 11.97; p = 0.01). The burden and stress of caregivers responsible for patients who participated in the intervention significantly decreased when compared to caregivers responsible for controls (Neuropsychiatric Inventory-Distress: F: 9.37; p = 0.01; Burden Interview: F: 11.28; p = 0.01). CONCLUSIONS: Aerobic exercise was associated with a reduction in the neuropsychiatric symptoms and contributed to attenuate the caregivers' burden. However, the researchers were not blinded to the patient's intervention status, which constitutes an important limitation of this study.
Keywords: Alzheimer's disease; Aerobic exercise; Neuropsychiatric symptoms; Caregiver's burden